LAND BANK MAINTAINS THE EXISTENCE OF LAND ACQUISITION FOR DEVELOPMENT - Sigit Sapto Nugroho; I Wayan Kartika Jaya Utama (NOTARIIL Jurnal Kenotariatan, 2022)
This study aims to analyze the urgency of land banks in maintaining the existence of land acquisition for development. This research method uses normative legal research methods with a statutory approach and a conceptual approach. The types and sources of legal materials used are primary, secondary and non-legal legal materials. The method of collecting legal materials uses the method of literature study. Analysis of legal materials using qualitative descriptive analysis. Based on the results of the study, it shows that the urgency of the Land Bank in land acquisition activities for development has the function of overcoming the problem of the form and value of compensation for land acquisition objects, preventing the growth of inventory of land needs for development activities for the public interest and reducing the implementation of land acquisition activities that require large costs and that take people's rights to their land.